Síntese, caracterização e avaliação catalítica do aluminossilicato mesoestruturado AI-MCM-41 na transesterificação de óleos vegetais - Pereira, Francisco de Assis Rodrigues (2010)
Molecular sieves have been applied to the processing of triacylglycerols, to produce biofuels. In this context, the mesoporous catalyst Al-MCM-41 was proposed in this work as an alternative to acid heterogeneous transesterification of cottonseed oil with ethanol. This material was prepared using various Si/Al molar ratios (25, 50, 75 and 100) with reaction times of 8, 10, 12 or 14 hours at 170°C. The solids were characterized by XRD, FTIR, 29 Si and 27Al MAS NMR, TG/DTA and nitrogen adsorption, which confirmed the mesoporous phase and allowed an estimate of the acidity associated whit the increase of aluminum content in the structure of MCM-41. The catalytic runs were carried out in a PAAR 4843 reactor, with an oil:ethanol molar ratio of 1:9 and catalyst loading of 1,5% at 200°C for 0-180 min; the reaction product was characterized by gas chromatography and 1H and 13C NMR. Gas chromatographic analysis, shoed that the conversion to ethyl esters is linearly dependent on catalyst loading, and Al-MCM-41 (Si/Al=50) was the most active material under the conditions tested. The results of GC-FID and 1H NMR analysis were corroborated by thermal analysis (TGA) and FTIR measurements, which were used to evaluate the Brønsted acidity of the materials. Overall, the yeld of the fatty acid ethyl ester (FAEE) transesterification increased with an increase in catalyst acidity.